Readers Theatre—Take Another Look—It’s More Than Fluency Instruction (LEARNing Landscapes, 2008)
This article argues that in spite of its benefits and value, there appears to be little attention given to the use of readers theatre or to its connection to theories of learning or reading. The author takes a "second look" at readers theatre and highlights its value in an attempt to reignite the excitement that it brings to reading. Social constructivism, Cambourne’s (1988) conditions for learning, and reader response theory are examined as the theoretical underpinnings. Using readers theatre increases comprehension, literature appreciation, and student engagement. Evidence is provided to support the claim that readers theatre is not only enjoyable for students, but it is also a sound pedagogy that results in more than improved fluency as reflected in the sample of student thoughts prefacing the next section.
Keywords: readers theatre; literature appreciation; reader response theory; social constructivism; learning; reading; fluency